Analysis of Science Learning Outcomes of Class VIII Students of Air Satan State Junior High School: Impact of Problem Based Learning Models - Hellen Anggraini; Ria Dwi Jayati; Harmoko Harmoko; Nur Hayati (Jurnal Penelitian Pendidikan IPA, 2022)
Many students have not yet completed the science learning process, so there is no need for students to take part in the improvement program to meet the Minimum completion criteria. The purpose of this study was to analyze the science learning outcomes of VIII-grade students of Air Setan Middle School through the Problem Based Learning model. The design of this study used a design that was created pretest-posttest Group Design. Samples are taken at random (simple random sampling). Data collection techniques using essay questions, this test is done twice, namely before (pre-test) and followed (post-test) learning process. Data analysis techniques using the t-test, in using this t-test, both the experimental class and the control class data must be normal and have a homogeneous variant that is tested for normality and homogeneity before testing the hypothesis with the t-test. Learning outcomes using problem-based learning are better because this learning involves students solving problems, by means of their creative ideas and ideas, so students do not easily forget the lessons they have learned